The Place of the Mihanović Psalter in the Fourteenth-Century Revisions of the Church Slavonic Psalter - MacRobert, Catherine Mary (Studia Ceranea, 2016)
Modern scholarship on the textual history of Church Slavonic biblical translation recognizes two distinct revisions of the Church Slavonic Psalter from the early fourteenth century, Redaction III (sometimes called the ‘Athonite’ redaction) and Redaction IV, known only in the Norov psalter manuscript. Although they are both attested from the same period and in manuscripts of similar Bulgarian provenance, these two redactions are in some respects systematically different in their linguistic character, their approach to translational issues and their Greek textual basis. In the light of A.A. Turilov’s observation that the Mihanović Psalter, possibly the earliest witness to Redaction III, is written in the same hand as the greater part of the Norov Psalter, this paper examines the textual antecedents of the two redactions and the importance of the Mihanović Psalter as a link between them.